Measuring the Dimensions of Environmental Perceptions of Citizens among High- Rise Building, Case Study: Tehran\'s 22th district - hamed behzadipour; zohre davoudpour; hossein zabihi (تحقیقات کاربردی علوم جغرافیایی)
High-rise buildings, by being recognizable in their context and signaling the introduction of urban integrity, have an impact on the perception and formation of citizens' mental image of the city. The present study examines the environmental perception of citizens in the interpretive, emotional, cognitive, and evaluative dimensions of high-rise buildings in Tehran’s 22th district as a case of study and emphasizes the formal, functional and semantic aspects of these buildings on citizen perception. The search system is intended for interpretive-structuralism research and the content analysis method (documentary method) is used in the theoretical section and the cross-sectional survey method. The population of the study consisted of 100 residents and non-residents of the area who are randomly selected. Data were analyzed by using SPSS software and Pearson correlation tests and one-sample T-test to evaluate the relationship between physical and semantic components in high-rise buildings perception and determine the importance of each environmental perception dimension.The results indicate that “the role of beauty of the form and shape of high-rise buildings” and “the amount of elevation congruence with the environment” in the first and second priorities affecting the level of citizens' environmental perception among physical and “The role of legibility and routing” as an effective factor among the semantic components in the perception of high-rise buildings has been based more on emotional and cognitive perception and less on the interpretative and perceptual dimensions of perceived citizenship.